Molecularly imprinted hydrogels from colloidal crystals for the detection of progesterone - Casis, Natalia (2014)
The synthesis of new nanoporous materials based on molecularly imprinted polymers (MIPs) is investigated. The novel procedure combines the non-covalent imprinting method with the colloidal crystal template technique to produce membranes with pre-specified morphology capable of selectively recognizing progesterone. The colloidal crystals made of silica particles were obtained by Langmuir − Blodgett and self-assembly techniques, and exhibited a considerable control of the film thickness. Hydrogel films were prepared by copolymerization of acrylic acid and ethylene glycol dimethacrylate in the presence of 2,2′-azobisisobutyronitrile as initiator. The polymerization took place in the interspaces of the colloidal crystal and after the reaction was finished the silica particles were etched with hydrofluoric acid to produce a 3D ordered structure. The nanocavities derived from progesterone were distributed within the walls of the internal structure of the films. The equilibrium swelling properties of the MIPs were studied as a function of crosslinking degree and pH. The pore morphology of the film was analyzed by SEM. The MIP characterizations were accomplished by several techniques, e.g. Fourier transform infrared spectroscopy, DSC and evaluation of their sensing and selective properties.